STRATEGIC ANALYSIS OF INFORMATION IN ENSURING ECONOMIC ECURITY OF EUROPEAN UNION COUNTRIES - Yeskov, Serge; Zaiets, Oleksandr; Kononenko, Yurii (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
The purpose of the article is to study the essence and stages of strategic analysis in ensuring economic security. Research methods: the use of system-structural method and the method of generalization allowed to analyze the general trends in the use of methods of strategic analysis. Using the dialectical method of scientific knowledge, as well as methods of analysis, synthesis and abstraction, the content and purpose of the research problem are clarified, its main features and structure, as well as the relationship with systems analysis are determined. Results: these methods of strategic analysis significantly increase the efficiency of forecasting the development of situations in the field of economic security due to the possibility of compiling a SWOT-analysis, PEST-analysis, etc. Discussion: in order to improve the system of strategic analysis, it is necessary to involve certain independent think tanks. Such think tanks should work closely with the authorities and be partially funded by the Government of Ukraine to obtain any necessary analytical information from them. Thus, the key issues of economic security are: the system of forecasting management activities; the process of research and analytical examinations; development of information and analytical products and their distribution; professional activity of specialists, professionals, analysts. Given the above, we conclude that the strategic analysis of public administration in the field of economic security is aimed at providing quality information to public authorities, and its improvement is impossible without studying the methodological principles of its formation. Analytical centers provide a link between government and civil society; represent and protect public interests; evaluate power and its decisions and formulate alternative policy proposals. Analytical centers are involved in the formation of European policy, promote better public understanding of EU regulations and decisions. The establishment of a domestic network of think tanks according to EU standards, which will be actively integrated into Euro-Atlantic networks of think tanks, will help find additional reserves to improve the mechanisms of strategic analysis in the field of economic security and state policy on effective forecasting and analytical support.